Concussive head injury exacerbates neuropathology of sleep deprivation: Superior neuroprotection by co-administration of TiO2-nanowired cerebrolysin, alpha-melanocyte-stimulating hormone, and mesenchymal stem cells - Sharma A.; Muresanu D.F.; Sahib S.; Tian Z.R.; Castellani R.J.; Nozari A.; Lafuente J.V.; Buzoianu A.D.; Bryukhovetskiy I.; Manzhulo I.; Patnaik R.; Wiklund L.; Sharma H.S. (My University, 2025)
Sleep deprivation (SD) is common in military personnel engaged in combat operations leading to brain dysfunction. Military personnel during acute or chronic SD often prone to traumatic brain injury (TBI) indicating the possibility of further exacerbating brain pathology. Several lines of evidence suggest that in both TBI and SD alpha-melanocyte-stimulating hormone (α-MSH) and brain-derived neurotrophic factor (BDNF) levels decreases in plasma and brain. Thus, a possibility exists that exogenous supplement of α-MSH and/or BDNF induces neuroprotection in SD compounded with TBI. In addition, mesenchymal stem cells (MSCs) are very portent in inducing neuroprotection in TBI. We examined the effects of concussive head injury (CHI) in SD on brain pathology. Furthermore, possible neuroprotective effects of α-MSH, MSCs and neurotrophic factors treatment were explored in a rat model of SD and CHI. Rats subjected to 48 h SD with CHI exhibited higher leakage of BBB to Evans blue and radioiodine compared to identical SD or CHI alone. Brain pathology was also exacerbated in SD with CHI group as compared to SD or CHI alone together with a significant reduction in α-MSH and BDNF levels in plasma and brain and enhanced level of tumor necrosis factor-alpha (TNF-α). Exogenous administration of α-MSH (250 μg/kg) together with MSCs (1 × 106) and cerebrolysin (a balanced composition of several neurotrophic factors and active peptide fragments) (5 mL/kg) significantly induced neuroprotection in SD with CHI. Interestingly, TiO2 nanowired delivery of α-MSH (100 μg), MSCs, and cerebrolysin (2.5 mL/kg) induced enhanced neuroprotection with higher levels of α-MSH and BDNF and decreased the TNF-α in SD with CHI. These observations are the first to show that TiO2 nanowired administration of α-MSH, MSCs and cerebrolysin induces superior neuroprotection following SD in CHI, not reported earlier. The clinical significance of our findings in light of the current literature is discussed. © 2020 Elsevier B.V.